High-resolution paleoenvironmental context for human occupations during the Middle Pleistocene in Europe (MIS 11, Germany). (15th May 2018) - Rivals, Florent; Ziegler, Reinhard
Abstract: High-resolution paleoecological proxies, such as stable isotopes or tooth microwear in large mammals, are often used for their potential to deliver information about the paleodietary traits of individuals and populations at the time of death. Such proxies are of interest in high resolution sites because they provide accurate data regarding the diet of large herbivores as well as the habitats that were available at the time of formation of the site, and by inference can detect seasonality in the formation of the assemblages. The integration of two techniques, tooth mesowear and microwear, applied to Middle Pleistocene assemblages of large herbivores from Steinheim and Heppenloch did not indicate seasonality at any of the two sites, most likely due to low resolution and time averaging of the dietary signal. However, the combination of the two proxies was highly informative for reconstructing the paleodiets of the large herbivores. The two paleodietary proxies provided consistent results that permitted us to propose a reconstruction of the paleodiets and habitats available at each site. Highlights: Dietary traits of the large herbivores from Steinheim indicate predominantly wooded habitats. Dietary traits of the large herbivores from Heppenloch indicate predominantly mixed habitats. Dietary traits are similar to those from other sites from the Hoxnian/Holsteinian interglacial. Tooth wear did not indicate seasonality due to low resolution and time averaging of the dietary signal.